Covert Investigative Activities in Kazakhstan: Purpose, Occurring Conflicts and Ways of their Overcoming - MATYSHOVA, Aigerim M. (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The present article is concerned with the legal origins of introducing covert investigative activities into the criminal procedural legislation of the Republic of Kazakhstan. A brief overview of the organized crime as the underlying cause for the appearance of such institution has been set forth. The experience of a number of foreign countries which have integrated the covert investigation methods into their laws has been analyzed. Different scholars’ opinions on the covert investigative activities have been studied. The issues of concern related to their integrating in the Republic of Kazakhstan have been summarized. Recommendations on changing the respective legal provisions of the Code of Criminal Procedure of the Republic of Kazakhstan have been provided thereupon.